Microbiological and Clinical Evaluation of the Efficacy of a Chemical Desiccant Agent in Non-Surgical Periodontal Treatment: A Randomized Controlled Clinical Trial - Alessia Pardo (Antibiotics, 2025)
Background: This randomized clinical trial compared the effects of topical irrigation with a desiccant agent (HybenX Oral Tissue Decontaminant, HBX) combined with full-mouth ultrasonic debridement as well as scaling and root planing (FMUD-SRP) versus conventional non-surgical periodontal therapy (US-SRP). Methods: Three quadrants per patient with probing pocket depth (PPD) ≥ 5 mm were randomly assigned to (i) the control group (US-SRP only), (ii) test group 1 (HBX + US-SRP at baseline, HBX 1T (one time)), or (ii) test group 2 (HBX + US-SRP across three sessions, HBX 3T (three times)). Clinical parameters included probing pocket depth (PPD), bleeding on probing (BOP), plaque index (PI), gingival recession (REC), and Clinical Attachment Level (CAL), recorded at baseline (Tbase), 45 days (T45d), and 90 days (T90d). Microbiological sampling was conducted for all sites at Tbase, T45d, and T90d to assess periodontal pathogens. HBX-treated sites received gel application for 60 s, followed by a saline rinse and US-SRP. Results: Significant differences were found between groups in PPD (p = 0.04) and CAL (p = 0.02) at T45d versus Tbase, while BOP, PI, and REC showed no significant inter-group differences at T45d. The HBX 3T group demonstrated greater pathogen reduction compared to the control and HBX 1T groups, except for one bacterial species. Conclusions: All treatments improved clinical and microbiological parameters. Even if single and triple applications of HBX showed similar clinical results, the repeated application achieved greater bacterial reduction.